What is the role of lateral lymph node dissection in rectal cancer patients with clinically suspected lateral lymph node metastasis after preoperative chemoradiotherapy? A meta‐analysis and systematic review - Xuyang Yang; Shuo Yang; Tao Hu; Chaoyang Gu; Mingtian Wei; Xiangbing Deng; Ziqiang Wang; Zongguang Zhou (Cancer Medicine)
Abstract Background Local lateral recurrence (LLR) in rectal cancer is increasingly becoming a significant clinical issue. Preoperative neoadjuvant chemoradiotherapy (nCRT) and lateral lymph node dissection (LLND)—when each approach is separately executed—cannot cure lateral lymph node metastasis (LLNM). Here, we performed a meta‐analysis to evaluate the efficacy of nCRT plus total mesorectal excision (TME) vs TME plus LLND after nCRT for rectal cancer. Methods Standard databases (PubMed, Embase, MEDLINE, Cochrane Library, and Web of Science) were searched to identify all relevant studies comparing nCRT+TME and nCRT+TME+LLND. Data in the included studies were extracted, and intraoperative outcomes, postoperative complications, and oncological outcomes were evaluated. Results Eight studies representing 1,896 patients (1,461 nCRT+TME vs 435 nCRT+TME+LLND) were included. We found that for patients with clinically suspected LLNM, the incidence of pathological LLNM was 27.8%, even after nCRT. LLND after nCRT was significantly associated with lower LLR (P = .02). Additional LLND yielded a longer operative time (P < .01) and increased the risk of urinary dysfunction (P < .01). Concerning other outcomes, no significant differences were identified between the two groups. Conclusion This is the first meta‐analysis and systematic review of studies comparing nCRT+TME and nCRT+TME+LLND for rectal cancer patients. Although increasing operative time and the risk of urinary dysfunction (which might be ameliorated by minimally invasive procedures), the pooled results support the use of LLND after nCRT and TME for reducing LLR in patients with clinically suspected LLNM and provide another treatment option for high‐risk patients.